SELF LEADERSHIP : SEBUAH PENDEKATAN - Fransisca Mulyono (Bina Ekonomi, 2012)
The concept of Self-leadership is considered to be a new approach when it first surfaced in the 1980's. Its principle is that the activity of a leader is no longer in the hands of few prominent members in the organization, but in the hands of all individuals in all levels of organization to motivate, direct and control himself/herself to perform positively as expected to achieve organization’s high competitive advantages through a conducive decision making process. Self-leadership capability has many advantages for the development of the organization, especially in this era of creativity, especially through the development of creative individuals. This paper attempts to outline some of the supporting factors for self-leadership development, its benefits, and in particular the strategies and methods needed to improve the ability of self-leadership.Key words : creativity and innovation, self-leadership, organizational commitment, self-leadership strategy.